Characteristics and transition mechanism of late Cenozoic structural deformation within the Niushoushan–Luoshan fault zone at the northeastern margin of the Tibetan Plateau. (15th December 2015) - Chen, Hong; Hu, Jianmin; Gong, Wangbin; Kang, Rui; Li, Libo
Graphical abstract: (a) NW strike sinistral fault in the NW–SE compression stress field in the Late Miocene–Pliocene, which indicate the southeastward tectonic extrusion in the late Miocene–Pliocene, caused by northward growth of the Tibetan Plateau and the westward subduction of the Pacific Plate. (b) NW and N–S strike dextral fault and NE strike sinistral fault in the NE–SW compression and NW–SE extension stress field in the Late Pliocene–Mid Pleistocene, which indicate Northwestward tectonic extrusion in the late Pliocene–mid Pleistocene, reflecting anti-clockwise rotation of the Ordos Block caused by the northeastward growth of the Tibetan Plateau. Highlights: New structural data reveal tectonic transition in late Cenozoic. Early sinistral deformation is related to tectonic extrusion. Later dextral deformation indicates the Tibetan Plateau expanding. Tibetan Plateau expanding northeastward as forward characteristics. Abstract: The Niushoushan–Luoshan fault zone (NLF) separates two major tectonic units: the Ordos Block and the northeastern margin of the Tibetan Plateau. The deformational processes within this fault zone recorded the uplift and expansion of the northeastern margin of the plateau. However, the tectonic transition mechanisms during the end Miocene–Pleistocene, and the characteristics of deformation at the end Pliocene and their tectonic significances, remain unclear. In this study, a detailed survey of structural deformation within the fault zone was carried out. The measurements were combined with regional tectonic analysis and geochronology to determine the effects of changing tectonic stress fields, and proposed the following late Cenozoic tectonic evolution of the NLF: NW–SE compression and left-lateral strike-slip deformation in the late Miocene–Pliocene; NE–SW compression and right-lateral strike-slip movement in late Pliocene–middle Pleistocene; and E–W extensional tectonics since the late Pleistocene. Although the late Miocene deformation indicates that expansion of the northeastern margin of the Tibetan Plateau had already reached this fault zone at this time, the most intense tectonic deformation did not commence until the end of the Pliocene. This indicates that the margin of the plateau was expanding at this time. The results show that the tectonic evolution of the NLF was closely related to collision between the Indian and Eurasian plates, and to uplift of the Tibetan Plateau. The fault zone also records the expansion of the northeastern margin of the Tibetan Plateau and the Cenozoic tectonic transition of the Ordos Block from westward extrusion to clockwise rotation.